KERENTANAN PANGAN TINGKAT DESA DI PROVINSI NUSA TENGGARA TIMUR - Tono, Tono; Juanda, Bambang; Barus, Baba; Martianto, Drajat (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
This study aimed to determine food vulnerability in the village level. This study was conducted by analysing 3,270 villages in Nusa Tenggara Timur (NTT) Province. Principal component analysis, cluster analysis and discriminant analysis were employed to classify the vulnerable villages. This study found that 1,468 villages (44.90%) were categorized as very vulnerable and vulnerable villages. Both categories were found mostly in Timor Tengah Selatan, Manggarai Timur, Manggarai Barat, Sumba Barat Daya, and Sumba Timur Regency. Food vulnerability enhancment programs need to be prioritized in very vulnerable and vulnerable villages in Timor Tengah Selatan, Manggarai Timur, Manggarai Barat, Sumba Barat Daya, and Sumba Timur Regency. Accessibility to electricity, clean water and sanitation facilities as well as the improvement of public welfare are key important factors to improve village food vulnerability.Keywords: cluster, food vulnerability, village